2008
DOI: 10.3748/wjg.14.1878
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing a low rate of hepatitis C viral RNA clearance in heroin users from Southern China

Abstract: INTRODUCTIONThe hepatitis C virus (HCV) epidemic now affects over 200 million people worldwide. HCV is a single-stranded RNA flavivirus that is responsible for the majority of non-A-non-B hepatitis infections [1,2] . Natural history studies have found that 15%-59% of people who are infected with HCV will undergo spontaneous viral clearance with no further liver disease due to HCV [3][4][5][6][7][8][9][10][11] . The remaining will develop chronic HCV infection that can lead to cirrhosis, hepatocellular carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Previously, Piyasirisilp et al [2000] and Tee et al [2008b] reported that both CRF07_BC and CRF08_BC were circulating among intravenous drug users in Baise City, a mountainous region near the Yunnan border of Guangxi Province. In addition, the prevalence of HCV infection among intravenous drug users infected with HIV-1 from Guangxi Province was more than 90% [Garten et al, 2004[Garten et al, , 2008. Although the major HIV subtypes found in the intravenous drug users in Taiwan and Guangxi are different (CRF07_BC in Taiwan and CRF08_BC in Guangxi), the association between the HCV strains from these two areas is very interesting.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, Piyasirisilp et al [2000] and Tee et al [2008b] reported that both CRF07_BC and CRF08_BC were circulating among intravenous drug users in Baise City, a mountainous region near the Yunnan border of Guangxi Province. In addition, the prevalence of HCV infection among intravenous drug users infected with HIV-1 from Guangxi Province was more than 90% [Garten et al, 2004[Garten et al, , 2008. Although the major HIV subtypes found in the intravenous drug users in Taiwan and Guangxi are different (CRF07_BC in Taiwan and CRF08_BC in Guangxi), the association between the HCV strains from these two areas is very interesting.…”
Section: Discussionmentioning
confidence: 97%
“…HCV positive subjects in China have low viral clearance rates [32]. The high rate of co-infection with HCV among HIV-1-infected patients represents a major challenge for the treatment of HIV-1-infected people in China [10], [33].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an ineffective early cell-mediated response may result in the development of chronic HCV infection. 24 In SRs, viral clearance is dependent on a complex set of viral-host interactions such as young age 25 ; females respond better than males, 26 host immune response and genetics, neutralizing antibodies, and viral specific factors that include genotypes, and diversity of quasispecies. 27 Partial protective immunity after spontaneous resolution of HCV infection has been reported, with lower rates of HCV reinfection than would be expected in a matched uninfected population.…”
Section: T Cellsmentioning
confidence: 99%